TEKS MANĀSIKUL HAJJI SEBAGAI PENYAMBUT KITAB MANĀSIKUL HAJJI WAL UMRAH WA ADAB AZ-ZIARAH LI SAYYIDIL MURSALĪN KARYA KIAI SHOLEH DARAT AS-SAMARANI (ANALISIS RESEPSI) - Syifaur Rohimah; Nur Fauzan Ahmad (Endogami: Jurnal Ilmiah Kajian Antropologi, 2022)
Hajj is the perfect worship of Islam which is the dream of all Muslims. So that the implementation of the pilgrimage is legal according to the law, a guidebook in the form of Hajj rituals is made. One of the ancient manuscripts containing Hajj rituals is the Manāsikul Hajji I by Ahmad Rivai and Manāsikul Hajji wal Umrah wa Adab Az-Ziyarah li Sayyidil Mursalīn by Kiai Sholeh Darat As-Samarani. This paper will examine philologically and reception with an intertextual approach to the two texts to find out how the relationship between the two texts is related. . Then the data is presented by descriptive method. The results of this study indicate that the book of Manāsikul Hajji as a welcoming text from the previous text, namely the book of Manāsikul Hajji wal Umrah wa Adab Az-Ziyarah li Sayyidil Mursalīn.